Desenvolvimento do Game Design Document de um Serious game para apoiar a educação em saúde de pacientes no transplante de células-tronco hematopoéticas - Sátiro, Luana Silva Pereira (2025)
Serious games are educational technologies with broad applicability in the health field. The relevance of this game is even more evident when considering hematopoietic stem cell transplantation, a therapy with high potential for morbidity and mortality due to its potential complications. An essential preliminary step for Serious games is the development of the Game Design Document, a descriptive material composed of content and dialogues. Thus, the research question was defined: How should the Game Design Document of a Serious game be structured to support health education for patients undergoing hematopoietic stem cell transplantation? In view of this, the objective was to develop the Game Design Document of a Serious game to support health education for patients undergoing hematopoietic stem cell transplantation. This is a methodological study with a quantitative approach, based on the psychometric framework of Pasquali et al (2010), which encompasses a set of three procedures: theoretical, empirical and analytical. For the theoretical procedures, a scoping review was carried out to map the contents for self-care of transplant patients; which took place between March and July 2024; and the Game Design Document was constructed with the selected contents between July and September 2024. The empirical procedures involved two phases for the evaluation of the psychometric properties, carried out between September and November 2024. In the first phase, the selection of expert judges was carried out, who were recruited through searches on the Lattes platform and who met the adapted Fehring criteria. In the second phase, the content of the Game Design Document was validated using the Delphi technique. This validation was carried out through a questionnaire via Google forms, in which the judges evaluated the criteria proposed by Pasquali et al. Finally, the analytical procedures were carried out by calculating the content validation coefficient and the level of agreement between the judges, carried out between November and December 2024. This study was previously approved by the Research Ethics Committee of the Federal University of Rio Grande do Norte and received a favorable opinion on May 8, 2024, under CAAE: 77538424.5.0000.5537. The ethical precepts of the research were followed and the anonymity of the participants was preserved. As the main results, guidelines were mapped that addressed the necessary care for the patient both in the hospital environment and at home. Thus, the initial and secondary interface and four scripts were constructed, namely: glossary, pre-, intra- and post-transplant period. After constructing the scripts that composed the Game Design Document, the material was submitted to the Delphi I and II stages for content validation. Thus, after Delphi II, the initial and secondary interfaces and scripts presented a content validation coefficient above 0.8 and an agreement level equal to or greater than 80%. Therefore, the Game Design Document was validated to compose a Serious game to support health education for patients undergoing hematopoietic stem cell transplantation. The study presents as a contribution the validated Game Design Document that will compose a Serious game to support health education for patients, in order to promote learning in an interactive and meaningful way, given the complexity to which these patients are exposed. It is emphasized that it is necessary to continue research to develop the Serious game, validate appearance, usability and effectiveness in order to prove the efficacy of the technology.